Nilai Pendidikan Karakter Tawaduk dalam Buku Kisah-Kisah Kesabaran Para Ulama Karya Syekh Abdul Fattah Bin Muhammad - Sugianti Sugianti; Mintarga Eman Surya (Proceedings Series on Social Sciences & Humanities, 2023)
Character education is an important part of education in Indonesia, the purpose of character education is to instill good character values in children. One of the important character values for children is the religious character which contains the value of a humble attitude which is important to grow in the child's soul. One of the media that can be a source of reference is a book that contains stories of pious people who exist today or in the past that can be learned from and are relevant in today's world of education. This research is a type of library research taken from a book by Sheikh Abdul Fattah bin Muhammad which was translated by Izzuddin Karimi with the title "Stories of the Patience of the Scholars". This study aimed to determine the value of character education in tawaduk, using data collection techniques in the form of documentation taken from primary and secondary data sources and then analyzing the content using inductive and deductive techniques to obtain results and conclusions. This study shows that the educational values of the tawaduk from the book are: 1) Not proud of oneself with rank/lineage, 2) Being friendly towards others, 3) Mingling with ordinary people, 4) being Modest in eating and drinking, 5) Likes to help/ Caring, 6) Good speech, 7) Study hard.